Illustrated dictionary of physics - Wertheim, Jane (Usborne London, 2006)
Suitable for students studying for their SATs and GCSE's, this title is split into 6 colour coded sections covering various aspects of the curriculum, such as radioactivity, heat, sound and electricity, as well as a general information section which includes essential charts and tables.